CIRI-CIRI KEUNTUNGAN MENURUT PERSPEKTIF ISLAM - Mohamad, Shamsiah (Jurnal Syariah, 2019)
Islam allows muslims to get profit from their daily transactions. Anyway this permissible is bounded with conditions because in Islam, profit has its own characteristics. Therefore, this article discusses the conditions of profit that has been stipulated by Islam.